2015
DOI: 10.1142/s0219877015500182
|View full text |Cite
|
Sign up to set email alerts
|

Gamification as an Intervention Method in Practice-Based Innovation

Abstract: This paper concentrates on the possibilities o®ered by gami¯cation in practice-based innovation activities. It addresses the following research questions: How does gami¯cation enhance creativity in practice-based innovation? How can gami¯cation be modi¯ed into a method that facilitates experiences of gamefulness? A case study presented in the paper examines the impact of gami¯cation in co-creating a value-adding network for open innovation processes between organizations. The results indicate that gami¯cation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 50 publications
0
12
0
1
Order By: Relevance
“…In fact, of the 15 publications selected, 17 case studies and one survey were considered. These studies, hereafter called cases, are referenced as: (1) Brandt et al (); (2) Hyypiä and Parjanen (); (3) Schulz et al (); (4) Scheiner (); (5) Kavaliova et al (); (6) Zimmerling et al (); (7) Agogué et al (); (8) Brandt et al (); (9) Gudiksen (); (10) Roos, Victor, and Statler (); (11) Vagn, Jensen, and Broberg (); (12) Grienitz and Schmidt (); (13) van Amstel and Garde (); (14) Kauppinen et al (); (15) Schulz et al (); (16) Patricio (); (17) Meijer (); and (18) Vagn et al (). A cross‐comparison was carried out, highlighting the similarities and the differences found between these 18 cases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, of the 15 publications selected, 17 case studies and one survey were considered. These studies, hereafter called cases, are referenced as: (1) Brandt et al (); (2) Hyypiä and Parjanen (); (3) Schulz et al (); (4) Scheiner (); (5) Kavaliova et al (); (6) Zimmerling et al (); (7) Agogué et al (); (8) Brandt et al (); (9) Gudiksen (); (10) Roos, Victor, and Statler (); (11) Vagn, Jensen, and Broberg (); (12) Grienitz and Schmidt (); (13) van Amstel and Garde (); (14) Kauppinen et al (); (15) Schulz et al (); (16) Patricio (); (17) Meijer (); and (18) Vagn et al (). A cross‐comparison was carried out, highlighting the similarities and the differences found between these 18 cases.…”
Section: Methodsmentioning
confidence: 99%
“…This research complements the emergent body of literature on design games in product and change management, Lego Serious Play in strategy, and serious games in management education (Roth, Schneckenberg, & Tsai, ). This line of research has shown that integrating gamification into innovation is a promising research avenue, particularly in ideation (Agogué, Levillain, & Hooge, ; Kavaliova, Virjee, Maehle, Kleppe, & Nisar, ), continuous innovation (Hyypiä & Parjanen, ), and serious play (Schulz, Geithner, Woelfel, & Krzywinski, ). These studies suggest that there is a need to research and further validate the actual value of gamification in relation to innovation, considering, in particular, its mechanics (rules) and participants' motivation (Brandt, Messeter, & Binder, ; Kavaliova et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Because open innovation embraces a variety of actors, not only crowds or consumers, Hyypiä and Parjanen (2015) conclude that gamification can be a useful approach in cocreating and enhancing collaboration among organizations. In the business context, gamification can also be applied to knowledge management as it has a positive impact on organizational results through reflecting, sharing and learning (Barnes & Milton, 2017) and supporting knowledge exchange, although gamification may not sufficiently support learning of the external knowledge required to attain high levels of originality (Agogué et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Gamification is an efficient tool to promote creativity and identify short‐term opportunities, easing outbound open innovation. Crowdsourcing activities can facilitate the gathering of information about the environment and contribute to open innovation implementation strategies (Armisen & Majchrzak, 2015; Milutinovic et al, 2018; Renard & Davis, 2019) and support cocreation with other stakeholders such as business partners (Hyypiä & Parjanen, 2015) and governments (Becker et al, 2019; Sandoval‐Almazan et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation